How does reverse shoulder replacement change proprioception in patients with cuff tear arthropathy?: a prospective optical 3D motion analysis study - Hetto, Pit; Bülhoff, Matthias; Sowa, Boris; Klotz, Matthias C. M.; Maier, Michael Wolfgang (Journal of orthopaedics, 2017)
Background: Reverse total shoulder arthroplasty (RSA) can improve function in cuff tear arthropathy (CTA) shoulders, but limited data are available on the effect of RSA on proprioception. The purpose of this study was the evaluation of the proprioception after RSA. Method: This study included fifteen consecutive patients (n=15) who received an RSA. We measured an active angle reproduction (AAR) by a novel 3D motion analysis using the Heidelberg upper extremity model (HUX). Results: The overall proprioception didn’t change significantly from 6.2° preoperatively to 6.2° postoperatively. Conclusion: We conclude that, the overall proprioception remained the same or deteriorated for different movements.
Available online 21 September 2017
Gesehen am 14.06.2018